2016
DOI: 10.1063/1.4964929
|View full text |Cite
|
Sign up to set email alerts
|

Automated electrorotation shows electrokinetic separation of pancreatic cancer cells is robust to acquired chemotherapy resistance, serum starvation, and EMT

Abstract: We used automated electrorotation to measure the cytoplasmic permittivity, cytoplasmic conductivity, and specific membrane capacitance of pancreatic cancer cells under environmental perturbation to evaluate the effects of serum starvation, epithelial-to-mesenchymal transition, and evolution of chemotherapy resistance which may be associated with the development and dissemination of cancer. First, we compared gemcitabine-resistant BxPC3 subclones with gemcitabine-naive parental cells. Second, we serum-starved B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 57 publications
0
14
0
2
Order By: Relevance
“…Improvements to ROT characterization through combining on‐chip analysis techniques, automation, and inclusion of cytoplasmic measurements have been shown [76–78]. Keim et al introduced an electrode array capable of simultaneous analysis of multiple‐ single cells.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%
“…Improvements to ROT characterization through combining on‐chip analysis techniques, automation, and inclusion of cytoplasmic measurements have been shown [76–78]. Keim et al introduced an electrode array capable of simultaneous analysis of multiple‐ single cells.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%
“…This template depends on five parameters: central time moment, t c ; transit time, δ; peak width control, σ; peak distance control, γ, and peak amplitude control, a. Parameters δ, σ, and γ are related to their space-domain counterparts respectively by δ = δ/v e , σ = σ/v e , and γ = γ/v e . The fitting parameters a, γ, and σ were used to compute the electrical diameter D and the relative prominence P , respectively from equations (3) and (6). In turn, the corrected electrical diameter D-corr was obtained from D and P by means of equation (10) or (9).…”
Section: Data Stream Processingmentioning
confidence: 99%
“…Electrical phenotyping offers a non-invasive method for the analysis and characterization of particles and cells on the basis of dielectric properties [2]. Besides conventional techniques like dielectrophoresis and electrorotation (e.g., [3,4,5,6]), the advent of microfluidic technology enabled the development of high-throughput microfluidic impedance cytometers (MICs). Typically, the core of a MIC is a microfluidic chip consisting of a microchannel equipped with microelectrodes and filled with a conductive buffer.…”
Section: Introductionmentioning
confidence: 99%
“…Even though impedance micro‐chambers for single biological cells have been developed , it can be shown that AC‐electrokinetic spectra have a higher resolution for the properties of freely suspended individual objects with the trade‐off of a higher field strength having to be employed in order to induce detectable movements . The movements can also be used for the separation of cells according to their properties . Moreover, AC‐electrokinetic force effects act on “smeared interfaces”, which may be generated by thermal gradients .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the frequency dependence of translations and rotations of single cells is microscopically analyzed in inhomogeneous (DEP) and rotating (ROT) external fields, respectively . From the DEP and ROT spectra, dielectric properties and cell physiological properties can be recalculated applying appropriate cell models. Such as for impedance, multi‐shell spherical, cylindrical and ellipsoidal models are readily available .…”
Section: Introductionmentioning
confidence: 99%